2019
DOI: 10.3390/app9010136
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing C-RAN Backhaul Topologies: A Resilience-Oriented Approach Using Graph Invariants

Abstract: At the verge of the launch of the first commercial fifth generation (5G) system, trends in wireless and optical networks are proceeding toward increasingly dense deployments, supporting resilient interconnection for applications that carry higher and higher capacity and tighter latency requirements. These developments put increasing pressure on network backhaul and drive the need for a re-examination of traditional backhaul topologies. Challenges of impending networks cannot be tackled by star and ring approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Emerging cyber-physical systems, such as medical devices that provide critical diagnostics and continuous therapeutic interventions to humans going about their daily lives [100] as well as networked vehicular systems [101][102][103], such as the transportation systems in smart cities, require uninterrupted connectivity with high quality of service levels. Wireless backhaul networks need multiple redundant connectivity paths that provide fail-over functionalities in case of failures [104][105][106]. Future backhaul resource optimization needs to account for and route among these multiple connectivity paths (e.g., with SDN support [107,108]) and optimally allocate resources during normal operation as well as after various failure scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging cyber-physical systems, such as medical devices that provide critical diagnostics and continuous therapeutic interventions to humans going about their daily lives [100] as well as networked vehicular systems [101][102][103], such as the transportation systems in smart cities, require uninterrupted connectivity with high quality of service levels. Wireless backhaul networks need multiple redundant connectivity paths that provide fail-over functionalities in case of failures [104][105][106]. Future backhaul resource optimization needs to account for and route among these multiple connectivity paths (e.g., with SDN support [107,108]) and optimally allocate resources during normal operation as well as after various failure scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…The sixth paper, authored by Frascolla et al and titled "Optimizing C-RAN Backhaul Topologies: A Resilience-Oriented Approach Using Graph Invariants" [10], proposes and investigates resilient 5G access network topologies. The network topology design is based on graph theory.…”
Section: Contributionsmentioning
confidence: 99%
“…It is found that the proposed optimization method shows superiority over other techniques. This method is also found to be effective in the telecommunication field as Frascolla et al use this method to optimize the C-RAN backhaul design [17]. Tauzowksi et al [18] propose a novel approach of functor-oriented topology optimization of elastoplastic structures.…”
Section: Introductionmentioning
confidence: 99%